Comparison of CDC, WHO and IOTF growth references in relation to overweight and obesity in college adolescents of North Karnataka, India - Bijendra Banjade; Vijaya A. Naik; Ashwini Narasannavar (Al Ameen Medical College, 2015)
Background and Objective: obesity has become a serious public health concern and is a key risk factor for the chronic and non-communicable disease. The objective of the study is to compare the various growth references in relation to overweight and obesity. Materaial &Methods: Weights and heights were measured on 330 adolescents and Body Mass Index (BMI) calculated. The prevalence of overweight and obesity was determined and statistical comparisons conducted among the three growth references; Centres for Disease Control (CDC), World Health Organization (WHO) and International Obesity Task Force (IOTF). Results: CDC and IOTF produced almost similar estimates of the prevalence of overweight, 9.1% versus 10.9% while WHO reported a higher prevalence 12.7%. In our study CDC and WHO classified twice as many as obese adolescents as compared to IOTF. There was a variable level of agreement between the references. Conclusions: The WHO reported a much higher prevalence of obesity compared to the other references. The prevalence of adolescent's obesity is dependent on the growth reference used.